Evaluating the Impact of ACLS Scenario Based Resuscitation Simulation for Emergency Team - Amatya, Yogendra; Shrestha, Susmita (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Medical simulation has become increasingly important for education in emergency situations like resuscitation and improvising healthcare services. Methods: A prospective study was performed implementing ACLS resuscitation simulation with the Patan Hospital emergency team. The survey questionnaire was designed to evaluate participants’ communication skills, leadership, team dynamics, competency in ACLS and perception regarding simulation as a learning method. The paired t-tests were performed to compare pre and post simulation survey responses. The quantitative data were managed and analysed using Microsoft Excel. Results: Fifty seven emergency staffs participated in the study. In the communication domain pre-simulation survey mean likert score of close loop communication was 2.68, SBAR was 2.54 and PEARL was 2.25 while the post-simulation survey were 3.19, 3.05 and 2.96 respectively. In leadership pre-survey assessment of coordinating team members was 2.61 and summarising events skill was 2.58 while the post-survey scores were 2.91 and 3.02 respectively. The team dynamics pre-survey of the teamwork experience was 2.63 while post-survey was 3.07. The competency pre-survey of competency level in ACLS was 2.51 while the post-survey was 2.88. The pre-survey regarding considering simulation a good method of training was 3.32 while the post-survey was 3.56. All the survey questionnaires of each domain showed the increased difference that is statically significant with p-values <0.001. Conclusions: Simulation training is an effective and useful educational technique for training the health personnel working in emergency service.